2019
DOI: 10.3390/pr7120931
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of the Effect of Al2O3 Content on the Liquid Phase Fluidity of Iron Ore Fines

Abstract: The sintering process is significantly important for the ironmaking in China because of the large amount of sinter consumed. Al2O3 is an important element determining the quality and quantity of sinter. However, different conclusions have been made regarding the effects of Al2O3 on the amount and fluidity of the liquid phase formed in the sinter phase. Therefore, it is necessary to examine the effects of Al2O3 content on the amount and fluidity of the liquid phase. The present work investigated the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…The similar SiO 2 and Al 2 O 3 contents of the sintered tablets of iron ores B and H lead to a similar SFCA amount of about 60%. Moreover, compared to the formation amount of SFCA of the sintered tablet of iron ore E with that of iron ore F, it is found that the exorbitant Al 2 O 3 content is adverse to SFCA formation on the condition of low SiO 2 content, in accordance with the results of previous investigations [9,44]. Meanwhile, the Al 2 O 3 content also affects the morphology of SFCA.…”
Section: Resultant Mineralogy and Microstructure Of Sintered Tabletssupporting
confidence: 88%
“…The similar SiO 2 and Al 2 O 3 contents of the sintered tablets of iron ores B and H lead to a similar SFCA amount of about 60%. Moreover, compared to the formation amount of SFCA of the sintered tablet of iron ore E with that of iron ore F, it is found that the exorbitant Al 2 O 3 content is adverse to SFCA formation on the condition of low SiO 2 content, in accordance with the results of previous investigations [9,44]. Meanwhile, the Al 2 O 3 content also affects the morphology of SFCA.…”
Section: Resultant Mineralogy and Microstructure Of Sintered Tabletssupporting
confidence: 88%
“…Comparing Figure 6b with Figure 6a, it is observed that the sinter macrostructure of the pressurized densification sintering process is much denser overall while that of the traditional sintering process remains rather looser especially for the lower part. This proves that heat accumulation behavior of limonitic laterite sintering from top to bottom is extremely poorer due to the high crystal water, MgO, and Al2O3 contents, resulting in the massive loss of heat [22][23][24][25]46]. As it turned out, the poor sintering performance of the product sinter of the traditional sintering process is obtained corresponding to the results of Figure 3.…”
Section: Sinter Porous Characterssupporting
confidence: 57%
“…However, although many experimental tests of limonitic laterite sintering have been carried out successfully and the relevant industrial production has already been achieved in Chinese research institutions and stainless-steel enterprises, the poor sintering performance of limonitic laterite remains a bottleneck to smooth production [17][18][19]. This is principally because the high crystal water (>30%) and LOI (>10%) contents of limonitic laterite contribute to the formation of highly porous loose sinter [20][21][22][23], and the massive existence of high-melting-point minerals, such as Al 2 O 3 , MgO, and Cr 2 O 3 is deleterious to liquid-phase flowing, leading to the substantial increase of solid fuel consumption [24][25][26][27]. Meanwhile, compared with ordinary iron ores, limonitic laterite possesses rather lower total iron content (40-50%), indicating the limited amount of liquid bonding phases [28][29][30][31]; all of which eventually lead to a poor tumble index (<50%), low productivity (<1.0 t•m −2 •h −1 ), and high solid fuel rate (>140 kg/t) of a product sinter of limonitic laterite.…”
Section: Introductionmentioning
confidence: 99%